"They have been neglected for a long time": a qualitative study on the role and recognition of rural health motivators in the Shiselweni region, Eswatini - Caroline Walker; Doris Burtscher; John Myeni; Bernhard Kerschberger; Bernadette Schausberger; Barbara Rusch; Nosipho Dlamini; Katherine Whitehouse (BMC, 2020)
Abstract Background Community health workers (CHWs) are increasingly engaged to address human resource shortages and fill primary healthcare gaps. In Eswatini, a cadre of CHWs called Rural Health Motivators (RHM) was introduced in 1976 to respond to key public health challenges. However, the emergence of health needs, particularly HIV/TB, has been met with inadequate programme amendments, and the role of RHMs has become marginalised following the addition of other CHWs supported by non-governmental organisations. This study was implemented to understand the role of RHMs in decentralised HIV/TB activities. In this paper, we explore the findings in relation to the recognition of RHMs and the programme. Methods This exploratory qualitative study utilised individual in-depth interviews, group and focus group discussions, participatory methods (utilising a game format) and observations. Participants were purposively selected and comprised RHM programme implementers, community stakeholders and local and non-governmental personnel. Data collection took place between August and September 2019. Interviews were conducted in English or siSwati and transcribed. SiSwati interviews were translated directly into English. All interviews were audio-recorded, manually coded and thematically analysed. Data was validated through methodical triangulation. Results Suboptimal organisational structure and support, primarily insufficient training and supervision for activities were factors identified through interviews and observation activities. Significant confusion of the RHM role was observed, with community expectations beyond formally endorsed tasks. Community participants expressed dissatisfaction with receiving health information only, preferring physical assistance in the form of goods. Additionally, gender emerged as a significant influencing factor on the acceptability of health messages and the engagement of RHMs with community members. Expectations and structurally limiting factors shape the extent to which RHMs are recognised as integral to the health system, at all social and organisational levels. Conclusions Findings highlight the lack of recognition of RHMs and the programme at both community and national levels. This, along with historical neglect, has hindered the capacity of RHMs to successfully contribute to positive health outcomes for rural communities. Renewed attention and support mechanisms for this cadre are needed. Clarification of the RHM role in line with current health challenges and clearer role parameters is essential.